Jus Kurma: Solusi Alami Menurunkan Hipertensi di RT 54 Kelurahan 16 Ulu - Suryaman, Agus; Latifah, Aulia Nurul; Dewi, Anggun Risma; Rianzah, Gilang; Eliyanti, Haliyah; Miranda, Melsha Febia; Natasya, Mirandaya (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2025)
Hypertension is a major health problem that can lead to serious complications if left untreated. One alternative solution is the use of date juice because it contains potassium, magnesium, fiber, and antioxidants that are good for heart and blood vessel health. This community service activity used an educational approach and a simple experiment through a pre-test and post-test design without a control on 32 hypertension sufferers. The intervention consisted of education and the consumption of date juice once daily for three days. The evaluation results showed a decrease in systolic blood pressure from 164.3 mmHg to 152.5 mmHg and diastolic blood pressure from 103 mmHg to 96.3 mmHg. These results indicate that date juice has the potential as an effective and affordable complementary therapy to help lower blood pressure in hypertension sufferers.